2022
DOI: 10.3389/fmars.2022.821646
|View full text |Cite
|
Sign up to set email alerts
|

Marine Heatwaves Characteristics in the Barents Sea Based on High Resolution Satellite Data (1982–2020)

Abstract: Marine heatwaves (MHWs) can potentially alter ocean ecosystems with far-reaching ecological and socio-economic consequences. This study investigates the spatiotemporal evolution of the main MHW characteristics in the Barents Sea using high-resolution (0.25° × 0.25°) daily Sea Surface Temperature (SST) data from 1982 to 2020. The results reveal that the Barents Sea has experienced accelerated warming and several more MHWs in recent decades. Since 2004, an amplified increasing SST trend was observed across the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 74 publications
6
34
0
Order By: Relevance
“…We detected multiple ECEs in recent years in the heat content of the upper water column in 2006, 2013, and 2016 as well as in June SIE in 2012. These results are confirmed by a recent study focusing specifically on marine heatwaves and using daily data of sea surface temperatures (SST) from 1982 to 2020 identified the same heatwaves in the Barents Sea in 2013 and 2016, negatively correlated with sea ice concentrations (Mohamed et al, 2022). Marine heatwaves in 2006 and 2012 were frequent in the north, but with a much lower cumulative intensity than 2013 and 2016.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…We detected multiple ECEs in recent years in the heat content of the upper water column in 2006, 2013, and 2016 as well as in June SIE in 2012. These results are confirmed by a recent study focusing specifically on marine heatwaves and using daily data of sea surface temperatures (SST) from 1982 to 2020 identified the same heatwaves in the Barents Sea in 2013 and 2016, negatively correlated with sea ice concentrations (Mohamed et al, 2022). Marine heatwaves in 2006 and 2012 were frequent in the north, but with a much lower cumulative intensity than 2013 and 2016.…”
Section: Discussionsupporting
confidence: 73%
“…Mohamed et al (2022) showed that marine heatwaves tended to be more frequent in the North of Barents Sea, and more intense and longer in the South. The 2006, 2012, and 2016 heatwaves were more frequent but less intense in the Northern Barents Sea than in the South (Mohamed et al, 2022). In our study, the relative change in environmental conditions in those years was also less extreme in the Atlantic than in the Arctic (Figure S9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations